1986
DOI: 10.1530/acta.0.1110433
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine profile of a long-acting somatostatin derivative SMS 201–995. Study in normal volunteers following subcutaneous administration

Abstract: The pharmacokinetics and the endocrine profile of a new low molecular somatostatin derivative, SMS 201\p=n-\995, were investigated in a group of 35 normal subjects. Clearance studies (n = 6) for this peptide showed a prolonged half-life in plasma, 113 min, following single sc injections of 50 or 100 \ g=m\ g. Arginine stimulation tests (n = 6) were conducted immediately and 180 min after sc injection of 50 \ g=m\ g of SMS 201\p=n-\995. The stimulatory effect of arginine on GH and insulin was counteracted by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(39 citation statements)
references
References 12 publications
3
35
1
Order By: Relevance
“…In a previous study, IGFBP-2 was found to be increased in many cancer patients (Kanety et al, 1993), and it is possible that the increase in this binding protein observed during tratment may be associated with disease progression rather than any influence of drug treatment. Somatostatin analogues are known to inhibit GH secretion (del Pozo et aL 1986). Surprisingly, we did not observe a consistent suppression of urinary GH in our patients.…”
Section: Statisticscontrasting
confidence: 79%
See 1 more Smart Citation
“…In a previous study, IGFBP-2 was found to be increased in many cancer patients (Kanety et al, 1993), and it is possible that the increase in this binding protein observed during tratment may be associated with disease progression rather than any influence of drug treatment. Somatostatin analogues are known to inhibit GH secretion (del Pozo et aL 1986). Surprisingly, we did not observe a consistent suppression of urinary GH in our patients.…”
Section: Statisticscontrasting
confidence: 79%
“…such effects could also be achieved through inhibition of growth factors and growth stimulatory hormones. Somatostatin analogues inhibit secretion of gastrointestinal hormones with possible mitogenic effects (Adrian et al 1981 ) and suppress synthesis of the insulin-like growth factor (IGF)-I (Pollak et al 1989: Figg et al 1995: Leo et al 1995 by suppressing growth hormone (GH) secretion (del Pozo et al 1986). the main trophic factor for IGF-I synthesis (Schwander et al 1983).…”
mentioning
confidence: 99%
“…This concentration can be achieved clinicly after a subcutaneous injection of at least 200 pg of octreotide repeated every 8 h. (Del Pozo et al, 1988). On the contrary, octreotide was generally adminired at a dose of 200 pg twice daily or 100-150 pg thrice daily, this corresponds to 60-75% of the optimal dose as judged from pharmacokinetic models (Del Pozo et al, 1986;Dy et al, 1992).…”
Section: Resutmentioning
confidence: 99%
“…* Significantly different from baseline values. subjects and patients with insulinoma (Del Pozo et al, 1986;Johnston et al, 1986;Stehouwer et al, 1989). Octreotide suppressed plasma glucagon concentrations in the control dogs but not in the dogs with insulinoma.…”
Section: Discussionmentioning
confidence: 86%
“…However, spontaneous (nocturnal) GH peaks (in humans) and stimulated GH responses to clonidine and human Growth Hormone Releasing Hormone (hGHRH, in dogs) and arginine (in humans) are lowered by octreotide (Del Pozo et al, 1986;Johnston et al, 1986;Selman et al, 1991). In dogs with insulinoma, a more detailed study of the pulsatile pattern of GH secretion is necessary to elucidate the effect of octreotide on spontaneous pulsatile GH release (Kooistra et al, 2000).…”
Section: Discussionmentioning
confidence: 99%